2017
DOI: 10.1111/1750-3841.13736
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation Characteristics and Aromatic Profile of Plum Wines Produced with Indigenous Microbiota and Pure Cultures of Selected Yeast

Abstract: The aim of this study was to assess and compare fermentation characteristics and aromatic profile of plum wines produced with indigenous microbiota and pure cultures of different selected yeast. Experiments were carried out with plum (Prunus domestica L.) varieties of different fruit ripening times (Čačanska rana, Čačanska lepotica, and Požegača). Wine fermentations were conducted by the activity of indigenous microbiota, commercially available Saccharomyces cerevisiae and Saccharomyces bayanus yeast strains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…A recent study investigating the alcoholic fermentation of S. cerevisiae showed that the reduced osmotic stress afforded by a fed-batch approach led to a 45% reduction in final glycerol and a 80% reduction in final acetic acid levels as compared with the traditional batch approach (Frohman & Mira de Orduña, 2013). In traditional batch fermentations, the S. pombe strain CECT11197 used in this study yielded acetic acid concentrations (0.55 g/L) that were similar to those reported by Mylona et al (2016) for another S. pombe strain (0.51 g/L for strains 7VA) but significantly lower than those reported by Miljić, Puškaš, Vučurović, and Muzalevski (2017) and Mylona et al (2016), for strains 2139 and 938 which exceeded 1 g/L of acetic acid. Conversely, Mylona et al (2016) and especially Du Plessis et al (2017) reported much lower levels for S. pombe strains than ranged between 0.07 g/L (expressed as volatile acidity) and 0.35 g/L acetic acid.…”
Section: Discussionsupporting
confidence: 70%
“…A recent study investigating the alcoholic fermentation of S. cerevisiae showed that the reduced osmotic stress afforded by a fed-batch approach led to a 45% reduction in final glycerol and a 80% reduction in final acetic acid levels as compared with the traditional batch approach (Frohman & Mira de Orduña, 2013). In traditional batch fermentations, the S. pombe strain CECT11197 used in this study yielded acetic acid concentrations (0.55 g/L) that were similar to those reported by Mylona et al (2016) for another S. pombe strain (0.51 g/L for strains 7VA) but significantly lower than those reported by Miljić, Puškaš, Vučurović, and Muzalevski (2017) and Mylona et al (2016), for strains 2139 and 938 which exceeded 1 g/L of acetic acid. Conversely, Mylona et al (2016) and especially Du Plessis et al (2017) reported much lower levels for S. pombe strains than ranged between 0.07 g/L (expressed as volatile acidity) and 0.35 g/L acetic acid.…”
Section: Discussionsupporting
confidence: 70%
“…In recent years, other industries have started to use Schizosaccharomyces species in products and processes other than the production of grape wine, such as ginger fermentation [106,107], apple wine [108], kei-apple fermentation [109], sparkling wine [110], bioethanol [111], bilberry fermentation [71], plum wine [112], and water purification [18].…”
Section: Schizosaccharomyces Speciesmentioning
confidence: 99%
“…with 0.25 µm film thickness) was used. The GC-FID conditions were previously described (Miljić, Puškaš, Vučurović, & Muzalevski, 2017).…”
Section: Analysesmentioning
confidence: 99%